Environmental risk factors, protective factors and lifestyles for lung cancer: an umbrella review - Minghao Feng; Feng Wang; Minwei Bao; Lei Zhu (Frontiers in Public Health, 2025)
BackgroundLung cancer remains a leading cause of cancer-related mortality worldwide, with environmental exposures and lifestyle factors playing a crucial role in its etiology. This umbrella review aims to systematically assess and classify the strength of evidence for environmental and lifestyle factors associated with lung cancer risk.MethodsA systematic search of published meta-analyses was conducted from database inception until January 31, 2025. Eligible meta-analyses included those evaluating associations between environmental or lifestyle exposures and lung cancer risk, with effect sizes reported as risk ratio (RR), odds ratios (OR), or standardized mortality ratios (SMR). The credibility of associations was assessed using statistical significance, heterogeneity (I2), small-study effects, and excess significance bias. The evidence was categorized into convincing (Class I), highly suggestive (Class II), suggestive (Class III), and weak or non-significant associations.ResultsA total of 58 meta-analyses covering 34 environmental factors and 24 lifestyle factors were included. Three environmental exposures—cadmium exposure (RR = 1.24, 95% CI: 1.18–1.29), diesel exhaust exposure (RR = 1.16, 95% CI: 1.13–1.18), and occupational exposure to paints (OR = 1.40, 95% CI: 1.29–1.51)—were classified as convincing evidence (Class I). Fifteen additional environmental factors, including secondhand smoke, benzene, formaldehyde, and indoor coal use, were classified as highly suggestive evidence (Class II). Among lifestyle factors, cooking-related exposures (OR = 1.21, 95% CI: 1.10–1.31) showed a convincing association with lung cancer risk, while dietary cholesterol intake (OR = 1.40, 95% CI: 1.20–1.64) and the Western dietary pattern (RR = 1.29, 95% CI: 1.01–1.66) were classified as highly suggestive evidence. Dietary patterns associated with reduced lung cancer risk included the Mediterranean diet (RR = 0.87, 95% CI: 0.82–0.93) and the prudent dietary pattern (RR = 0.80, 95% CI: 0.64–0.96), both of which were significantly associated with lower lung cancer risk. Heterogeneity was substantial in 48.57% of environmental associations and 39.13% of lifestyle associations, highlighting potential confounding factors.ConclusionThis umbrella review highlights multiple environmental and lifestyle exposures with strong or suggestive associations with lung cancer. These findings support stricter environmental regulations, workplace protections, and lifestyle interventions. Future research should prioritize biomarker-based exposure assessments and long-term cohort studies to refine risk estimates and inform prevention strategies.Systematic review registrationThe study is registered with PROSPERO, number 1003974.